2020
DOI: 10.3400/avd.oa.20-00113
|View full text |Cite
|
Sign up to set email alerts
|

Neomedia Repair of the Valsalva Sinus in the Treatment of Acute Type-A Aortic Dissection: Long-term Effectiveness and a Case of Pathology

Abstract: Although numerous surgical techniques are employed to treat acute Stanford type A aortic dissection (ATAAD), controversy remains over which is the best procedure for aortic root reconstruction. Among the various techniques utilized, neomedia repair is considered to be more promising than adhesive-only repair for the treatment of a dissected aortic root. We experienced a series of neomedia sinus Valsalva repair using woven polyester fabric, and evaluated the aortic root diameter by computed tomography and sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Our study showed that the severity of AI grade (group A: P < 0.001; group B: P < 0.001) and the enlargement of aortic root (group A: P < 0.001; group B: P = 0.005) were ameliorated in both groups after surgery [Figure S2 and S3], indicating both surgical techniques could improve the durability of aortic root and short-term effects, given AI and enlargement of proximal aorta could increase the risk of aortic root reoperation. [11] A multiple logistic regression analysis, considering these relevant confounding factors, indicated a signi cant correlation between the primary endpoint events and the surgical technique (OR, 0.002, 95%CI, 0-0.159; P = 0.026). This suggests that group A tended to have reduced 30-day mortality and a lower risk of reoperation for hemostasis.…”
Section: Discussionmentioning
confidence: 96%
“…Our study showed that the severity of AI grade (group A: P < 0.001; group B: P < 0.001) and the enlargement of aortic root (group A: P < 0.001; group B: P = 0.005) were ameliorated in both groups after surgery [Figure S2 and S3], indicating both surgical techniques could improve the durability of aortic root and short-term effects, given AI and enlargement of proximal aorta could increase the risk of aortic root reoperation. [11] A multiple logistic regression analysis, considering these relevant confounding factors, indicated a signi cant correlation between the primary endpoint events and the surgical technique (OR, 0.002, 95%CI, 0-0.159; P = 0.026). This suggests that group A tended to have reduced 30-day mortality and a lower risk of reoperation for hemostasis.…”
Section: Discussionmentioning
confidence: 96%
“…Although no significant differences were observed in 30-day mortality between the two groups ( P = 0.110), the 30-day mortality in group A was nil. Our study showed that the severity of AI grade (group A: P < 0.001; group B: P < 0.001) and the enlargement of aortic root (group A: P < 0.001; group B: P = 0.005) were ameliorated in both groups after surgery [Figure S3 and S4], indicating both surgical techniques could improve the durability of aortic root and short-term effects, given AI and enlargement of proximal aorta could increase the risk of aortic root reoperation [ 11 ].…”
Section: Discussionmentioning
confidence: 99%